1972
DOI: 10.1136/jnnp.35.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Habituation: effects of regular and stochastic stimulation

Abstract: S U M MARY The different effects of regular and stochastic stimulation on the flexor reflex of patients with the spinal cord totally divided and of normal subjects and on the blink reflex of normal subjects were studied.When the cutaneous stimulus was above but less than twice threshold, with regular stimulation habituation occurred; with stochastic stimulation, habituation either did not occur or it was minimal. Stochastic stimulation was at random stimulus intervals or with random stimulus intensities.When s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 12 publications
5
37
1
Order By: Relevance
“…Habituation is most pronounced for low stimulus intensities (Dimitrijevic et al 1972), as observed in the present study. Alternatively, the tendency for re¯exes of lower amplitude to occur could also re¯ect a lowering of the arousal level as the volunteers adapt to experimental conditions.…”
Section: Discussionsupporting
confidence: 60%
“…Habituation is most pronounced for low stimulus intensities (Dimitrijevic et al 1972), as observed in the present study. Alternatively, the tendency for re¯exes of lower amplitude to occur could also re¯ect a lowering of the arousal level as the volunteers adapt to experimental conditions.…”
Section: Discussionsupporting
confidence: 60%
“…It was shown that this pattern of repetitive reflex stimulation prevents habituation of the flexor reflex responses. 6,12,14,24 The successive reflex responses obtained before TENS application and those elicited after placebo-TENS in this study did not show a significant tendency to decrease on repetitive stimulation. We may therefore conclude that the observed decrease of flexor reflex responses following TENS application to the area of the sural nerve cannot be attributed to the process of habituation.…”
Section: Discussioncontrasting
confidence: 49%
“…Similar results were already reported in previous reflex studies, where it was discover that a proper selection of the stimulation parameters, e.g. random inter-stimulus intervals, stimulation of different sites and varying stimulation intensities, can prevent reflexes from habituating ( (Dimitrijević et al, 1972;Granat et al, 1991).…”
Section: Fixed Vs Adjusted Stimulation Intensitiessupporting
confidence: 86%